Primer aislamiento de Clostridium tetani a partir de suelos de la Meseta Central de Costa Rica - Rodríguez, Evelyn (Universidad de Costa Rica, 1991)
Clínical evidence has long pointed to the existence of Clostridium tetani in Costa Rica. Thirty soil samples were studied for clostridia, and two yielded six strains of C. tetani, four of which proved to be toxigenic when mice were inoculated intraperitoneally with the culture supemates, These four isolates could be neutralized when their toxic supemates were admixed with tetanus antitoxin.